Pengajaran Dasar Membaca, Berhitung, Mengaji dan Bahasa Inggris untuk Anak Anak Desa Mekar Sari - Anandanaz, Tria; Munandar, Riki; Azhari, Diah; Asnawati, Asnawati; Rulyanti, Merry; Nur’aini, Hesti; Fariadi, Herri (LPPM Universitas Dehasen Bengkulu, 2025)
Children’s education in Mekar Sari Village faces significant challenges due to low learning motivation caused by conventional teaching methods. The implemented educational program aims to enhance student motivation and involvement through an interactive, character-based learning approach. This method involves the use of visual media, educational games, and a fun learning environment. The results show that the interactive approach can improve students’ learning interest, enhance literacy and numeracy skills, and foster positive character development. Additionally, collaboration between educators, the community, and village leaders proves essential for the sustainability and success of the program. These findings align with previous studies indicating that character-based education strengthens student motivation. This program is expected to serve as a model for other villages to improve the quality of basic education in remote areas.